PROPOSAL OF PHYSICALTHERAPY PREVENTIVE INTERVENTION TO THE OSTEOMUSCULAR DISTURBANCES RELATED TO THE WORK (Fiep Bulletin - online, 2014)
The occupational disturbances are nowadays a problem of public health, taking the employee to the temporary removal of the work and sometimes to permanent. The prevention lack and attendance adapted the worker bring damages as the pain, the insecurity, fear of losing the employment, psyco-social and financial problems, besides damages for the employer and for the Union. Therefore, the objective of this work went verify a preventive program of preparatory exercises for the work day it facilitates benefits the worker's health. We used a preparatory program of exercises in 14 employees of the Faculdade União das Americas of Foz do Iguaçu, PR, Brazil, and we analyzed aspects as: width of shoulder movement, elbow, knee and hip; pain intensity before and after the accomplishment of the exercises and effects after the accomplishment of the program. We verified an improvement of 41,94% in the pain and 14,03% in the movement width in the individuals that accomplished the program frequently of superior participation at 70%, it improves coordination and in the inter-personal relationship. We can conclude that a preventive program of exercises can promote benefits the worker's health, minimizing painful pictures, improving flexibility and posture, besides developing the inter-personal relationships.
Keywords: LRE / ODRT; preventive; exercises work